1993
DOI: 10.1002/abio.370130205
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pressure on the growth of methanotrophic bacteria

Abstract: The growth rate and the maximum cell concentration of methanotrophic bacteria are limited by the transfer of methane and oxygen to the culture fluid. The operation under moderate pressure results in an increase in driving force for the mass transfer of both nutrients and, therefore, in a large increase in the attainable biomass concentration. Our laboratory pressure fermenter with a volume of 12 litres operates under a system pressure of up to 0.5 MPa. In this reactor a maximum productivity of 6 g biomass/lh i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Moreover, in the present work, the air pressure increase stimulated cell growth due to higher oxygen availability in the medium. Several authors have shown that use of increased air or oxygen pressure is an efficient means of oxygenation improvement in various microbial cell cultures (Yang and Wang 1992;Wendlandt et al 1993;Lee et al 1997;Belo and Mota 1998;Pinheiro et al 2003). However, there are limits for the air or oxygen pressure increase depending on the microorganism and strain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the present work, the air pressure increase stimulated cell growth due to higher oxygen availability in the medium. Several authors have shown that use of increased air or oxygen pressure is an efficient means of oxygenation improvement in various microbial cell cultures (Yang and Wang 1992;Wendlandt et al 1993;Lee et al 1997;Belo and Mota 1998;Pinheiro et al 2003). However, there are limits for the air or oxygen pressure increase depending on the microorganism and strain.…”
Section: Discussionmentioning
confidence: 99%
“…The oxygen solubility in the liquid medium can also be raised by the increase of the total air pressure in the cultivation system. Bioreactor headspace pressurization has been proved to be an efficient way of OTR improvement for different microbial cell strains (8)(9)(10)(11). However, there are limits for oxygen partial pressure rise in a cell culture due to the oxidative stress caused by oxygen (12).…”
Section: Introductionmentioning
confidence: 99%